Affinities in Paint : Work by Appel - Auerbach - Bacci - Bogart - Bowling - de Staël - Doucet - Dubuffet - Jorn - Hofmann - Hoyland - Kossoff - Olitski - Tapies also Rouault, Soutine, Bomberg. - McEwen, John (London : Crane Gallery, 1991)
Appel - Auerbach - Bacci - Bogart - Bowling - de Staël - Doucet - Dubuffet - Jorn - Hofmann - Hoyland - Kossoff - Olitski - Tapies also Rouault, Soutine, Bomberg
Affinities in Paint : Work by Appel - Auerbach - Bacci - Bogart - Bowling - de Staël - Doucet - Dubuffet - Jorn - Hofmann - Hoyland - Kossoff - Olitski - Tapies also Rouault, Soutine, Bomberg, Crane Gallery, London, 14 June - 31 July 1991
boek